2020
DOI: 10.2298/psi190129012d
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet and Facebook use and online gaming among university students: An exploratory study

Abstract: Advances in technology have introduced new challenges and issues for policymakers and researchers. There is some debate in the literature whether the Internet, Facebook, and online gaming addictions may be true addiction disorders or are all manifestations of a more general information technology addiction. The purpose of this study is to explore gender differences in problematic Internet and Facebook use and online gaming, and the independence of these phenomena. The study sample comprised 500 college student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…At the national level, research on the subject is still poorly developed compared to the international panorama, focusing mainly on social media and online videogames [2,56]. However, studies have shown that-despite affecting a small percentage of individuals-Internet addiction is a reality that, in Portugal, mainly affects teenagers and young adults in school and university, thus requiring intervention and the prevention of addictive behaviors in these contexts [43,57].…”
Section: The Internet and Digital Platforms In Young People's Livesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the national level, research on the subject is still poorly developed compared to the international panorama, focusing mainly on social media and online videogames [2,56]. However, studies have shown that-despite affecting a small percentage of individuals-Internet addiction is a reality that, in Portugal, mainly affects teenagers and young adults in school and university, thus requiring intervention and the prevention of addictive behaviors in these contexts [43,57].…”
Section: The Internet and Digital Platforms In Young People's Livesmentioning
confidence: 99%
“…In this sense, the pandemic context in which we live carries increased risks for young people who have seen their freedom and sociability become limited to their homes and dependent on the online world. Several studies at the international level have crossed the field of psychology and communication to analyze possible changes in media use during the pandemic, focusing on the potential consequences of excess or a lack of quality [12,14,15,17,45,57,58]. Although these were sometimes preliminary studies of an ongoing phenomenon, they allow us to identify risk factors and issues that require attention and long-term investigation by the academic community and public health authorities.…”
Section: The Internet and Digital Platforms In Young People's Livesmentioning
confidence: 99%
“…A nível nacional, o seu estudo é ainda pouco desenvolvido, comparativamente com o panorama internacional, com foco principal em usos de redes sociais e videojogos online (Pontes, Patrão, & Griffiths, 2014;Dias, et al, 2017;2018). Contudo, estudos recentes (Pontes & Griffiths, 2014;Pontes, Andreassen, & Griffiths, 2016, Dias et al, 2020 têm evidenciado que, apesar de afetar uma percentagem reduzida de indivíduos, a dependência da Internet é uma realidade que, em Portugal, afeta principalmente utilizadores adolescentes e jovens adultos, em contexto escolar e universitário, sendo necessário uma intervenção e prevenção de comportamentos aditivos nestes contextos.…”
Section: A Internet E Os Jovens Em Contexto Pandémicounclassified